Learning about the Functions of the Olfactory System from People without a Sense of Smell - Croy, Ilona (Public Library of Science, 2012)
The olfactory system provides numerous functions to humans, influencing ingestive behavior, awareness of environmental hazards and social communication. Approximately ⅕ of the general population exhibit an impaired sense of smell. However, in contrast to the many affected, only few patients complain of their impairment. So how important is it for humans to have an intact sense of smell? Or is it even dispensable, at least in the Western world? To investigate this, we compared 32 patients, who were born without a sense of smell (isolated congenital anosmia - ICA) with 36 age-matched controls. A broad questionnaire was used, containing domains relevant to olfaction in daily life, along with a questionnaire about social relationships and the BDI-questionnaire. ICA-patients differed only slightly from controls in functions of daily life related to olfaction. These differences included enhanced social insecurity, increased risk for depressive symptoms and increased risk for household accidents. In these domains the sense of olfaction seems to play a key role.